Entity information life cycle for big data : master data management and information integration - Talburt, John R.; Zhou, Yinle, 1986- (Waltham, MA : Elsevier : Morgan Kaufmann, 2015)
Entity Information Life Cycle for Big Data walks you through the ins and outs of managing entity information so you can successfully achieve master data management (MDM) in the era of big data. This book explains big data's impact on MDM and the critical role of entity information management system (EIMS) in successful MDM. Expert authors Dr. John R. Talburt and Dr. Yinle Zhou provide a thorough background in the principles of managing the entity information life cycle and provide practical tips and techniques for implementing an EIMS, strategies for exploiting distributed processing to handle big data for EIMS, and examples from real applications. Additional material on the theory of EIIM and methods for assessing and evaluating EIMS performance also make this book appropriate for use as a textbook in courses on entity and identity management, data management, customer relationship management (CRM), and related topics.
Appendix A -- Some Commonly Used ER Comparators.
Vendor-supplied metadata.
Includes bibliographical references and index.
Keywords: Big data; Semantic Web; Pattern recognition systems; Data mining; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Big data; Data mining; Pattern recognition systems; Semantic Web; Electronic books; Electronic books